Factors Associated with Healthy Toilet Ownership in Drien Kipah Village, Southwest Aceh Regency - Ulvani; Kiswanto Kiswanto; Yulizar Yulizar; Darmawan Darmawan; Danvil Nabela (PT.Mantaya Idea Batara, 2025)
Having a healthy toilet is basic sanitation that must be had in all househodsl. This research aims to determine the factors related to the ownership of healthy latrines. This research uses quantitative research with a cross sectional design. The sample in this research A total of 87 samples were obtained using a simple random sampling technique using the Slovin formula. The results of the research show that there is a relationship between the level of community knowledge and ownership of healthy latrines in Drien Kipah Village, Southwest Aceh Regency. There is a relationship between the level of knowledge and ownership of healthy latrines, p-value= 0.003 (OR=0.266), there is no relationship between attitudes and ownership of latrines. healthy with p-value=0.371, (OR=1.474), there is no relationship between education and ownership of a healthy latrine with pvalue=0.843 (OR=0.896) and there is no relationship between income and ownership of a healthy latrine with p-value value= 0.458 (OR=1.516).